International Cooperation of States in the Field of Internally Displaced Persons Protection - D. V. Ivanov (Московский журнал международного права, 2011)
This article outlines history of international legal regulation of internally displaced persons (IDPs) protection; main theoretical aspects of the subject in question and examples of successful regional cooperation in the field of IDPs protection.